Norway : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
A conservative minority government took office in October 2013, ending eight years of Labor party-led governments. No major policy shift has taken place so far, but the government's economic policy platform emphasizes lower taxes, more infrastructure investment, greater private ownership, and measures to improve productivity and competitiveness. New challenges are emerging as oil-related investment is peaking and competitiveness concerns are becoming more pressing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet